Determinant Factors of TikTok Live Streaming Host Communication on Purchase Decisions - Ineke Febrianti; Nur Hayati (Almana : Jurnal Manajemen dan Bisnis, 2026)
The rapid expansion of social commerce through TikTok Live has transformed digital marketing practices in the fashion industry, particularly in Indonesia where platform adoption is highly significant. Live streaming enables real-time interaction between hosts and consumers, making communication a critical factor in influencing purchasing behavior. However, the role of host communication in shaping consumer decisions remains underexplored. Therefore, this study aims to examine the influence of host communication dimensions credibility, attractiveness, message clarity, and interaction on consumer purchase decisions for Kukai fashion products through TikTok Live. This study applies a mixed methods approach with an explanatory sequential design, combining qualitative exploration and quantitative verification. The findings indicate that host communication significantly shapes consumer trust, engagement, and understanding during live streaming sessions. In particular, clear message delivery and interactive communication play a central role in encouraging purchase decisions. This study highlights the importance of effective communication strategies in live streaming commerce and provides insights for brands to optimize host performance in enhancing consumer engagement and purchase outcomes.